2011
DOI: 10.1128/jvi.00245-11
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Specific Contributions to Mumps Virus Neurovirulence and Neuroattenuation

Abstract: Mumps virus (MuV) is highly neurotropic and was the leading cause of aseptic meningitis in the WesternHemisphere prior to widespread use of live attenuated MuV vaccines. Due to the absence of markers of virus neuroattenuation and neurovirulence, ensuring mumps vaccine safety has proven problematic, as demonstrated by the occurrence of aseptic meningitis in recipients of certain vaccine strains. Here we examined the genetic basis of MuV neuroattenuation and neurovirulence by generating a series of recombinant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…MuV JL5 -London was characterised by the expansion of variants present at low frequency in the original vaccine, two of which have previously been described [8], as well as fixed de novo mutations in the M, N, P, L and F genes, a finding which again references those described for MV in SSPE. While most amino acid substitutions occurred in the M gene, in vitro data using the rat model implicates the F protein [3,16] as key for mumps virus neurovirulence in acute encephalitis [16,24] as well as for measles neurovirulence in SSPE [3]. The absence of within-host sequence diversity in the M and F ORFs ( Figure S5, Table S7) further suggests functional constraints on these genes and supports directional selection acting on one or more of the amino acid changes in these proteins favouring spread and replication of MuV JL5 in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…MuV JL5 -London was characterised by the expansion of variants present at low frequency in the original vaccine, two of which have previously been described [8], as well as fixed de novo mutations in the M, N, P, L and F genes, a finding which again references those described for MV in SSPE. While most amino acid substitutions occurred in the M gene, in vitro data using the rat model implicates the F protein [3,16] as key for mumps virus neurovirulence in acute encephalitis [16,24] as well as for measles neurovirulence in SSPE [3]. The absence of within-host sequence diversity in the M and F ORFs ( Figure S5, Table S7) further suggests functional constraints on these genes and supports directional selection acting on one or more of the amino acid changes in these proteins favouring spread and replication of MuV JL5 in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently limited data available on sequencing of the full-length genomes of attenuated MuV vaccine strains. Although it was recently indicated that N/M proteins are involved in viral pathogenicity/attenuation of MuV (Sauder et al, 2011), these patterns have not been observed in all strains (Lemon et al, 2007;Malik et al, 2009;Liang et al, 2010;Xu et al, 2012). As a result, no unique differentiation marker has been found between parental wild and attenuated passages of different vaccine strains.…”
Section: Resultsmentioning
confidence: 90%
“…The major genetic determinant of neurovirulence of the rodent-adapted Kilham strain appears to be the F gene [42]. While the neurovirulence of the wild-type MuV isolate 88-1961 seems to be a multigenic trait [43]. Such a scenario was described with the 88-1961 strain, where an additive effect on neuroattenuation of the two mutations – one in the HN protein and one in the L polymerase protein – was demonstrated [37].…”
Section: Resultsmentioning
confidence: 98%